High Average Power High-Harmonic EUV Sources and High Performance Imaging at the Nanoscale - Limpert Jens; Rothhardt Jan (EPJ Web of Conferences)
We will report about the development of fiber-laser-driven high harmonic sources with output power currently exceeding 10 mW. This exceptional performance, combined with structured illumination approaches, enables nanoscale imaging and mapping of the chemical composition of semiconductor- and biological samples at the nanoscale.